(untitled) (Acta Polytechnica CTU Proceedings, 2016)
The second version of railway standard EN50128:2011 published by CENELEC is used for five years and thus the CENELEC reasons about preparation of new version of this standard are coming, because the CENELEC defined 10-year cycle of its standards innovation. The paper discusses some observations of problems of this standard application from the position of safety assessor which gives us the contact with developers applying this standard into the real railway products.